Relationship between building maintenance sourcing strategy selection factors and performance - Soh, Khai Ying; Chua, Shirley Jin Lin; Ali, Azlan Shah; Au-Yong, Cheong Peng; Alias, Anuar (Emerald, 2019)
Purpose: The building maintenance management becomes more complicated nowadays, with several sourcing strategies springing up for building maintenance work provisions. Various studies demonstrate that the selection factors and performance measurements are both essential aspects in determining and evaluating the sourcing strategy for building maintenance management. Thus, the purpose of this paper is to examine the relationships between the selection factors and performance measurements of sourcing strategy. Design/methodology/approach: The paper targeted to evaluate and analyse the perceptions of the building maintenance practitioners regarding the degree of importance of selection factors and performance measurements. Through quantitative approach, the paper adopted stratified random sampling to distribute the questionnaires to the building maintenance practitioners operating in both private and government high-rise office buildings in Kuala Lumpur. Findings: The findings highlighted the quality factors as the most important selection group factors; meantime, the ability to fulfil client’s need and requirement as well as the ability to deliver the service with reasonable reliability and predictability are identically important performance measurements. There is a significant relationship between the selection factors and performance measurement of sourcing strategy. Originality/value: This paper provides an impetus research which uncovered the sourcing practices in the industry and guided the sourcing process in determining the appropriate sourcing strategy. © 2019, Emerald Publishing Limited.